Publication of maps on the Internet: the evolution of cartography - Olga Sergeevna Anikeeva (Наука. Инновации. Технологии, 2022)
The article describes the evolution of the technologies used in cartography. It analyzed the concept of cartography, mapping and integration of information technologies, the emergence of such a thing as the Internet mapping. Dan's first classification of the maps presented in the Internet. The history of the development of web-mapping since 1993. A brief description of projects such as Xerox PARC Map Viewer, a national atlas of Canada, an atlas of Scotland, virtual globe NASA World Wind, Open Street Maps, global mapping services Google-Maps and Google-Earth. Among the projects highlighted in Russian projects such as WikiMapia, 2GIS project, which includes a map, business directory, travel options in the various forms of transport, etc., search and information service Yandex, which allows to watch maps of major cities and satellite images, reference -Information service «public cadastral map» that provides users with information of the State cadastre of real estate in Russia. The analysis and classification of the main advanced applications to create Web mapping solutions. Among them are custom geographic information systems, mapping resources to quickly create and publish spatial data, as well as Web servers and geo-portals, which are ready-made solutions to well-deined user interface.